Polarizing plate with retardation layer, and image display device using the same
By using a directional cured layer composed of liquid crystal compounds as the retardation layer on the extremely thin polarized filter plate, and adjusting the material composition and process parameters, the problem of cracks easily occur during the heating process of the extremely thin polarized filter plate is solved, and the efficient crack prevention and good optical performance of the extremely thin polarized filter plate is achieved.
Patent Information
- Application Number
- JP2024224626
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-08-06
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to prevent cracks from occurring during the heating process while maintaining extremely thinness, and it is difficult to take into account good optical properties.
When a protective layer is not provided on the opposite side of the extremely thin polarized filter plate, a directional cured layer composed of liquid crystal compounds is used as the retardation layer of the polarized filter plate, and by adjusting the material composition and process parameters of the polarized filter plate, the unidirectional mittance and polarization of the polarized filter plate are ensured to reach a suitable range.
It is realized that the extremely thin polarized filter plate is not prone to cracks during heating, while maintaining good optical performance, including high unidirectional mittance and polarization.
Smart Images

Figure 2025038188000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate with a retardation layer, and an image display device using the same. [Background technology]
[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), have rapidly become widespread. Image display devices usually use a polarizing plate and a retardation plate, each of which includes a polarizer and a protective layer for protecting the polarizer. In practice, a retardation layer-attached polarizing plate, in which a polarizing plate and a retardation plate are integrated, is widely used (e.g., Patent Document 1). Recently, as the demand for thinner image display devices increases, the demand for thinner retardation layer-attached polarizing plates also increases.
[0003] As a method for making a polarizing plate thinner, it has been proposed to reduce the thickness of the protective layer and to laminate a protective layer only on one side of the polarizer. However, these methods cannot sufficiently protect the polarizer, there is room for improvement in durability, and there are problems in that the polarizer is easily cracked by heat treatment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-343521 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above-mentioned problems in the conventional art, and its main object is to provide a polarizing plate with a retardation layer that is thin and yet suppresses the occurrence of cracks when heated. [Means for solving the problem]
[0006] According to one aspect of the present invention, there is provided a polarizing plate with a retardation layer, comprising a polarizer and a retardation layer provided on one side of the polarizing plate, the polarizing plate does not include a protective layer on the side of the polarizer opposite to the side on which the retardation layer is provided, the retardation layer is an oriented and solidified layer of a liquid crystal compound, the polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic material, and when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin is y, the following formula (1) is satisfied: y<-0.011x+0.525 (1) According to another aspect of the present invention, there is provided a polarizing plate with a retardation layer, comprising a polarizer and a retardation layer provided on one side of the polarizing plate, wherein the polarizing plate does not include a protective layer on the side of the polarizer opposite to the side on which the retardation layer is provided, the retardation layer is an oriented and solidified layer of a liquid crystal compound, the polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic material, and wherein, when a single transmittance is x% and an in-plane retardation of the polyvinyl alcohol-based resin film is z nm, the following formula (2) is satisfied: z<-60x+2875 (2) According to yet another aspect of the present invention, there is provided a polarizing plate with a retardation layer, comprising a polarizer and a retardation layer provided on one side of the polarizing plate, wherein the polarizing plate does not include a protective layer on the side of the polarizer opposite to the side on which the retardation layer is provided, the retardation layer is an orientation and solidification layer of a liquid crystal compound, the polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic material, and wherein, when a single transmittance is x% and an orientation function of the polyvinyl alcohol-based resin is f, the following formula (3) is satisfied: f<-0.018x+1.11 (3) According to yet another aspect of the present invention, there is provided a polarizing plate with a retardation layer, comprising a polarizing plate including a polarizer and a retardation layer provided on one side of the polarizing plate, the polarizing plate does not include a protective layer on the side of the polarizer opposite to the side on which the retardation layer is provided, the retardation layer is an alignment solidified layer of a liquid crystal compound, and the piercing strength of the polarizer is 30 gf / μm or more. In one embodiment, the retardation layer-attached polarizing plate has a total thickness of 30 μm or less. In one embodiment, the polarizer has a thickness of 10 μm or less. In one embodiment, the polarizer has a single transmittance of 40.0% or more and a polarization degree of 99.0% or more. In another aspect of the present invention, there is provided an image display device including the above-mentioned retardation layer-attached polarizing plate. Effect of the Invention
[0007] According to the present invention, by using a polarizer in which the orientation state of a polyvinyl alcohol (PVA)-based resin is controlled, even if a protective layer is not provided on at least one side of the polarizer, the occurrence of cracks during heating can be suppressed, and as a result, a polarizing plate with a retardation layer that is extremely thin and yet suppresses the occurrence of cracks during heating can be obtained. Moreover, such a polarizer can exhibit optical properties that are acceptable for practical use. [Brief description of the drawings]
[0008] [Figure 1A] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Figure 1B] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Figure 1C] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Figure 1D] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a drying shrinkage treatment using a heating roll in a manufacturing method of a polarizer used in the retardation layer-attached polarizing plate of the present invention. [Diagram 3] FIG. 2 is a graph showing the relationship between the single transmittance of the polarizers produced in the examples and comparative examples and the birefringence of the PVA-based resin. [Figure 4] FIG. 2 is a graph showing the relationship between the single transmittance of the polarizers produced in the Examples and Comparative Examples and the in-plane retardation of the PVA-based resin films. [Diagram 5]FIG. 2 is a graph showing the relationship between the single transmittance of the polarizers produced in the examples and comparative examples and the orientation function of the PVA-based resin.
[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments. In addition, each embodiment can be appropriately combined.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0011] A. Overall structure of the polarizing plate with a retardation layer The polarizing plate with a retardation layer according to the embodiment of the present invention has a polarizing plate including a polarizer and a retardation layer provided on one side of the polarizing plate, and the retardation layer is an alignment solidified layer of a liquid crystal compound. Schematic cross-sectional views of an example of the polarizing plate with a retardation layer according to the embodiment of the present invention are respectively shown in Figures 1A to 1D.
[0012] 1A includes a polarizing plate 10 and a retardation layer 20 provided on one side of the polarizing plate 10. The polarizing plate 10 includes a polarizer 11 and a protective layer 12 provided on the retardation layer 20 side, and no protective layer is provided on the side opposite to the side on which the retardation layer 20 is provided.
[0013] 1B includes a polarizing plate 10 and a retardation layer 20 provided on one side of the polarizing plate 10. The polarizing plate 10 includes a polarizer 11, and no protective layer is provided on either side of the polarizing plate 10.
[0014] The retardation layer-attached polarizing plate 100C illustrated in FIG. 1C has a polarizing plate 10 and a retardation layer 20 provided on one side of the polarizing plate 10. The polarizing plate 10 includes a polarizer 11, and no protective layer is provided on either side of the polarizing plate 10. The retardation layer 20 has a laminated structure of a first alignment solidified layer 21 and a second alignment solidified layer 22.
[0015] FIG. 1D is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to yet another embodiment of the present invention. In the retardation layer-attached polarizing plate 100D illustrated in FIG. 1D, in addition to the polarizing plate 10 and the retardation layer 20 (the first alignment solidified layer 21 and the second alignment solidified layer 22), another retardation layer 30 and a conductive layer (or a conductive layer-attached isotropic substrate) 40 are provided in this order on the side of the retardation layer 20 opposite to the side on which the polarizing plate 10 is provided. The other retardation layer 30 typically exhibits a relationship of nz>nx=ny in terms of refractive index characteristics. The other retardation layer 30 and the conductive layer (or the conductive layer-attached isotropic substrate) 40 are typically any layers provided as necessary, and either one or both may be omitted. For convenience, the retardation layer 20 may be referred to as the first retardation layer, and the other retardation layer 30 may be referred to as the second retardation layer. In addition, when a conductive layer or an isotropic substrate with a conductive layer is provided, the polarizing plate with a retardation layer can be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (e.g., an organic EL cell) and a polarizing plate.
[0016] The polarizing plate with a retardation layer according to the embodiment of the present invention may further include other retardation layers. The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other retardation layers can be appropriately set according to the purpose.
[0017] The polarizing plate with a retardation layer according to the embodiment of the present invention may be in a sheet shape or a long shape. In this specification, the term "long" means a long and narrow shape whose length is sufficiently long relative to its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, relative to its width. The long polarizing plate with a retardation layer can be wound into a roll.
[0018] For practical purposes, a pressure-sensitive adhesive layer (not shown) is provided on one or both outer surfaces of the retardation layer-attached polarizing plate, specifically, on the outer surface of the image display cell side and / or the opposite side (typically, the viewing side) of the retardation layer-attached polarizing plate, so that it can be attached to an adjacent member. Furthermore, it is preferable that a release film is temporarily attached to the surface of the pressure-sensitive adhesive layer until the retardation layer-attached polarizing plate is used. By temporarily attaching the release film, the pressure-sensitive adhesive layer is protected and roll formation is possible.
[0019] The total thickness of the retardation layer-attached polarizing plate is preferably 30 μm or less, more preferably 25 μm or less, and further preferably 20 μm or less. The total thickness may be, for example, 10 μm or more. According to the embodiment of the present invention, such an extremely thin retardation layer-attached polarizing plate can be realized. Furthermore, the occurrence of cracks during heating can also be suppressed. In addition, such a retardation layer-attached polarizing plate can have extremely excellent flexibility and bending durability. Therefore, such a retardation layer-attached polarizing plate can be particularly suitably applied to a curved image display device and / or a bendable or foldable image display device. The total thickness of the retardation layer-attached polarizing plate refers to the sum of the thicknesses of all layers constituting the retardation layer-attached polarizing plate, excluding the adhesive layer for adhering the retardation layer-attached polarizing plate to an external adherend such as a panel or glass (i.e., the total thickness of the retardation layer-attached polarizing plate does not include the thickness of the adhesive layer for attaching the retardation layer-attached polarizing plate to an adjacent member such as an image display cell and the thickness of the release film that can be temporarily attached to the surface of the adhesive layer).
[0020] The unit weight of the retardation layer-attached polarizing plate according to the embodiment of the present invention is, for example, 6.5 mg / cm 2 or less, preferably 2.0 mg / cm 2 ~6.0mg / cm 2 and more preferably 3.0 mg / cm 2 ~5.5mg / cm 2 , and more preferably 3.5 mg / cm 2 ~5.0mg / cm 2 When the display panel is thin, the weight of the polarizing plate with a retardation layer may cause the panel to deform slightly, resulting in display defects.2 The retardation layer-attached polarizing plate having the following unit weight can prevent such deformation of the panel. The retardation layer-attached polarizing plate having the above unit weight has good handleability even when it is thinned, and can exhibit extremely excellent flexibility and bending durability.
[0021] The components of the retardation layer-attached polarizing plate will be described in more detail below.
[0022] B. Polarizing plate The polarizing plate includes a polarizer made of a PVA-based resin film containing a dichroic material. The polarizing plate may or may not further include a protective layer on the side of the polarizer on which the retardation layer is provided, but does not include a protective layer on the side opposite to the side on which the retardation layer is provided. By omitting the protective layer on at least one side, preferably both sides, and employing an oriented and solidified layer of a liquid crystal compound as the retardation layer, an extremely thin polarizing plate with a retardation layer can be obtained.
[0023] B-1.Polarizer The polarizer is composed of a PVA-based resin film containing a dichroic material. In one embodiment, the polarizer satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin constituting the polarizer is y. In one embodiment, the polarizer satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film constituting the polarizer is z nm. In one embodiment, the polarizer satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin constituting the polarizer is f. In one embodiment, the piercing strength of the polarizer is 30 gf / μm or more. y<-0.011x+0.525 (1) z<-60x+2875 (2) f<-0.018x+1.11 (3)
[0024] The birefringence of the PVA resin in the polarizer (hereinafter referred to as the birefringence of PVA or Δn of PVA), the in-plane retardation of the PVA resin film (hereinafter referred to as the "in-plane retardation of PVA"), the orientation function of the PVA resin (hereinafter referred to as the "orientation function of PVA"), and the piercing strength of the polarizer are all values related to the degree of orientation of the molecular chain of the PVA resin constituting the polarizer. Specifically, the birefringence, in-plane retardation, and orientation function of PVA can become large with an increase in the degree of orientation, and the piercing strength can decrease with an increase in the degree of orientation. The polarizer used in the present invention (i.e., a polarizer satisfying the above formulas (1) to (3) or the piercing strength) is suppressed from thermally shrinking in the absorption axis direction due to the fact that the molecular chain of the PVA resin is more gently oriented in the absorption axis direction than in conventional polarizers. As a result, a retardation layer-attached polarizing plate that is extremely thin and yet suppresses the occurrence of cracks during heating can be obtained. In addition, since such a polarizer has excellent flexibility, a polarizing plate with a retardation layer having excellent flexibility and bending durability can be obtained, and the polarizing plate can be preferably applied to a curved image display device, more preferably a bendable image display device, and even more preferably a foldable image display device. Conventionally, it has been difficult to obtain acceptable optical properties (typically, single transmittance and polarization degree) with a polarizer having a low degree of orientation, but the polarizer used in the present invention can achieve both a lower degree of orientation of the PVA-based resin than conventional ones and acceptable optical properties.
[0025] The polarizer used in the present invention preferably satisfies the following formula (1a) and / or formula (2a), and more preferably satisfies the following formula (1b) and / or formula (2b). -0.004x+0.18 <y<-0.011x+0.525 (1a) -0.003x+0.145 <y<-0.011x+0.520 (1b) -40x+1800 <z<-60x+2875 (2a) -30x+1450 <z<-60x+2850 (2b)
[0026] In this specification, the in-plane retardation of the PVA is the in-plane retardation value of the PVA-based resin film at 23°C and a wavelength of 1000 nm. By using the near-infrared region as the measurement wavelength, it is possible to eliminate the influence of iodine absorption in the polarizer and to measure the retardation. In addition, the birefringence (in-plane birefringence) of the PVA is the value obtained by dividing the in-plane retardation of the PVA by the thickness of the polarizer.
[0027] The in-plane retardation of PVA is evaluated as follows: First, the retardation value is measured at multiple wavelengths of 850 nm or more, and the measured retardation value: R(λ) is plotted against the wavelength: λ, and this is fitted to the Sellmeier equation below by the least squares method. Here, A and B are fitting parameters and are coefficients determined by the least squares method. R(λ)=A+B / (λ 2 -600 2 ) In this case, the retardation value R(λ) can be separated into an in-plane retardation value (Rpva) of PVA that has no wavelength dependency and an in-plane retardation value (Ri) of iodine that has strong wavelength dependency, as shown below. Rpva= A Ri = B / (λ 2 -600 2 ) Based on this separation formula, the in-plane retardation (i.e., Rpva) of PVA at a wavelength λ=1000 nm can be calculated. The method for evaluating the in-plane retardation of PVA is also described in Japanese Patent No. 5932760, and can be referred to as necessary. In addition, the birefringence (Δn) of the PVA can be calculated by dividing this retardation by the thickness.
[0028] Commercially available devices for measuring the in-plane retardation of PVA at a wavelength of 1000 nm include the KOBRA-WR / IR series and KOBRA-31X / IR series manufactured by Oji Measurement Co., Ltd.
[0029] The orientation function (f) of the polarizer used in the present invention preferably satisfies the following formula (3a), and more preferably satisfies the following formula (3b): If the orientation function is too small, an acceptable single-unit transmittance and / or degree of polarization may not be obtained. -0.01x+0.50 <f<-0.018x+1.11 (3a) -0.01x+0.57 <f<-0.018x+1.1 (3b)
[0030] The orientation function (f) is determined, for example, by attenuated total reflection (ATR) measurement using a Fourier transform infrared spectrophotometer (FT-IR) and polarized light as the measurement light. Specifically, germanium is used as the crystallite to which the polarizer is attached, the incident angle of the measurement light is 45°, the incident polarized infrared light (measurement light) is polarized light (s-polarized light) that vibrates parallel to the surface to which the germanium crystal sample is attached, and the measurement is performed with the stretch direction of the polarizer arranged parallel and perpendicular to the polarization direction of the measurement light. -1 The intensity I is calculated according to the following formula using the intensity of 3330 cm -1 is used as the reference peak, and 2941 cm -1 / 3330cm -1 The value is 2941 cm. Note that f=1 is perfect alignment, and f=0 is random. -1 The peak is due to the main chain (-CH) of PVA in the polarizer. 2 It is believed that this absorption is due to vibrations of the -. f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) however, c = (3cos 2 β-1) / 2, 2941cm -1 For vibration, β=90°. θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I⊥ ) / (I / / ) (In this case, the more the PVA molecules are oriented, the larger D becomes.) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel
[0031] The thickness of the polarizer is preferably 10 μm or less, and more preferably 8 μm or less. The lower limit of the thickness of the polarizer may be, for example, 1 μm. The thickness of the polarizer may be 2 μm to 10 μm in one embodiment, and 2 μm to 8 μm in another embodiment. By making the thickness of the polarizer so thin, it is possible to make the thermal shrinkage very small. It is presumed that such a configuration may also contribute to suppressing the occurrence of cracks due to heating.
[0032] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more, more preferably 41.0% or more. The upper limit of the single transmittance may be, for example, 49.0%. In one embodiment, the single transmittance of the polarizer is 40.0% to 45.0%. The degree of polarization of the polarizer is preferably 99.0% or more, more preferably 99.4% or more. The upper limit of the degree of polarization may be, for example, 99.999%. In one embodiment, the degree of polarization of the polarizer is 99.0% to 99.9%. One of the features of the polarizer used in the present invention is that the degree of orientation of the PVA-based resin constituting the polarizer is lower than that of a conventional polarizer, and the polarizer has the above-mentioned in-plane retardation, birefringence, and / or orientation function, yet the polarizer can achieve such a single transmittance and degree of polarization that are practically acceptable. This is presumably due to the manufacturing method described later. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and corrected for visibility. When measuring the single transmittance of a polarizer using a polarizing plate having a configuration of [polarizer / resin substrate (protective layer)], the single transmittance of the polarizer is a value obtained by converting the refractive index of one surface of the polarizing plate to 1.50 and the refractive index of the other surface to 1.53. The polarization degree is typically calculated by the following formula based on the parallel transmittance Tp and crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and corrected for visibility. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0033] The piercing strength of the polarizer is, for example, 30 gf / μm or more, preferably 35 gf / μm or more, more preferably 40 gf / μm or more, even more preferably 45 gf / μm or more, and particularly preferably 50 gf / μm or more. The upper limit of the piercing strength can be, for example, 80 gf / μm. By setting the piercing strength of the polarizer in such a range, it is possible to significantly suppress the occurrence of cracks in the polarizer when heated and the polarizer from tearing along the absorption axis direction. As a result, a polarizer (and, as a result, a polarizing plate) with very excellent flexibility can be obtained. The piercing strength indicates the crack resistance of the polarizer when the polarizer is pierced with a predetermined strength. The piercing strength can be expressed, for example, as the strength (breaking strength) at which the polarizer breaks when a predetermined needle is attached to a compression tester and the needle is pierced into the polarizer at a predetermined speed. As is clear from the unit, the piercing strength means the piercing strength per unit thickness (1 μm) of the polarizer.
[0034] As described above, the polarizer is composed of a PVA-based resin film containing a dichroic material. Preferably, the PVA-based resin constituting the PVA-based resin film (substantially the polarizer) contains an acetoacetyl-modified PVA-based resin. With such a configuration, a polarizer having a desired piercing strength can be obtained. The blending amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, when the entire PVA-based resin is taken as 100% by weight. If the blending amount is within such a range, the piercing strength can be set to a more suitable range.
[0035] A polarizer can be typically produced using a laminate of two or more layers. A specific example of a polarizer obtained using a laminate includes a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch the laminate. Furthermore, the stretching preferably further includes stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In an embodiment of the present invention, the total stretching ratio is preferably 3.0 to 4.5 times, which is significantly smaller than normal. Even at such a total stretching ratio, a polarizer having acceptable optical properties can be obtained by adding a halide and combining it with a dry shrinkage treatment. Furthermore, in an embodiment of the present invention, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the boric acid water stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even at a small total stretching ratio. In addition, the laminate is preferably subjected to a dry shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. In one embodiment, the method for producing a polarizer includes subjecting the laminate to an auxiliary air stretching treatment, a dyeing treatment, an underwater stretching treatment, and a dry shrinkage treatment in this order. By introducing the auxiliary stretching, even when a PVA-based resin is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA-based resin, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution when the resin is immersed in water in the subsequent dyeing and stretching processes can be prevented, making it possible to achieve high optical properties.Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing process and an underwater stretching process. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage process. The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate and any suitable protective layer may be laminated on the peeled surface according to the purpose. Details of the method for producing a polarizer will be described in detail in Section B-2.
[0036] B-2. Manufacturing method of polarizer The method for producing the polarizer preferably includes forming a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a halide and a polyvinyl alcohol-based resin (PVA-based resin) on one side of a long thermoplastic resin substrate to form a laminate, and subjecting the laminate to an auxiliary air stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order, in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. The content of the halide in the PVA-based resin layer is preferably 5 parts by weight to 20 parts by weight with respect to 100 parts by weight of the PVA-based resin. The drying shrinkage treatment is preferably performed using a heating roll, and the temperature of the heating roll is preferably 60° C. to 120° C. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 2% or more. Furthermore, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the underwater stretching. According to such a production method, the polarizer described in the above item B-1 can be obtained. In particular, a laminate including a PVA-based resin layer containing a halide is prepared, the laminate is stretched in multiple stages including auxiliary air stretching and underwater stretching, and the stretched laminate is heated with a heating roll to shrink the laminate by 2% or more in the width direction, thereby obtaining a polarizer having excellent optical properties (typically, single transmittance and polarization degree).
[0037] B-2-1. Preparation of laminate Any suitable method can be adopted as a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer. Preferably, a coating liquid containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate, and then dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.
[0038] Any appropriate method can be used as the coating method of the coating liquid. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. are listed. The coating and drying temperature of the coating liquid is preferably 50° C. or higher.
[0039] The thickness of the PVA-based resin layer is preferably 2 μm to 30 μm, and more preferably 2 μm to 20 μm. By making the thickness of the PVA-based resin layer before stretching very thin in this manner and reducing the total stretching ratio as described below, a polarizer having an acceptable single transmittance and polarization degree can be obtained despite the degree of orientation of the PVA-based resin being lower than in the past.
[0040] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.
[0041] B-2-1-1. Thermoplastic resin base material Any suitable thermoplastic resin film may be used as the thermoplastic resin substrate. Details of the thermoplastic resin substrate are described in, for example, JP 2012-73580 A. The entire disclosure of this publication is incorporated herein by reference.
[0042] B-2-1-2. Coating liquid The coating liquid contains a halide and a PVA resin as described above. The coating liquid is typically a solution in which the halide and the PVA resin are dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, water is preferred. The concentration of the PVA resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin.
[0043] Additives may be added to the coating liquid. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These can be used to further improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.
[0044] Any appropriate resin may be adopted as the PVA-based resin. Examples include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined in accordance with JIS K 6726-1994. By using a PVA-based resin having such a saponification degree, a polarizer having excellent durability can be obtained. If the saponification degree is too high, gelation may occur. As described above, the PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin.
[0045] The average degree of polymerization of the PVA resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.
[0046] Any suitable halide may be used as the halide. For example, iodide and sodium chloride may be used. For example, iodide may be potassium iodide, sodium iodide, and lithium iodide. Among these, potassium iodide is preferred.
[0047] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin, and more preferably 10 to 15 parts by weight per 100 parts by weight of the PVA-based resin. If the amount of the halide exceeds 20 parts by weight per 100 parts by weight of the PVA-based resin, the halide may bleed out, causing the finally obtained polarizer to become cloudy.
[0048] Generally, the orientation of polyvinyl alcohol molecules in the PVA-based resin layer increases when the PVA-based resin layer is stretched, but when the stretched PVA-based resin layer is immersed in a liquid containing water, the orientation of polyvinyl alcohol molecules may be disturbed and the orientation may decrease. In particular, when a laminate of a thermoplastic resin substrate and a PVA-based resin layer is stretched in boric acid water, the tendency of the orientation degree to decrease is significant when the laminate is stretched in boric acid water at a relatively high temperature to stabilize the stretching of the thermoplastic resin substrate. For example, the stretching of a PVA film alone in boric acid water is generally performed at 60°C, whereas the stretching of a laminate of A-PET (thermoplastic resin substrate) and a PVA-based resin layer is performed at a high temperature of about 70°C, in which case the orientation of PVA at the initial stage of stretching may decrease before it increases due to underwater stretching. In response to this, a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate is prepared, and the laminate is stretched at high temperature (auxiliary stretching) in air before being stretched in boric acid water, so that the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a process such as a dyeing process and an underwater stretching process.
[0049] B-2-2. Aerial supplementary stretching process In particular, in order to obtain high optical properties, a two-stage stretching method is selected, which combines dry stretching (auxiliary stretching) and stretching in boric acid water. By introducing auxiliary stretching like two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate. Furthermore, when applying a PVA-based resin on a thermoplastic resin substrate, it is necessary to lower the application temperature compared to when applying a PVA-based resin on a normal metal drum in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, and as a result, the crystallization of the PVA-based resin becomes relatively low, and a problem that sufficient optical properties cannot be obtained may occur. On the other hand, by introducing auxiliary stretching, it is possible to increase the crystallinity of the PVA-based resin even when applying a PVA-based resin on a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution can be prevented when immersed in water in the subsequent dyeing process or stretching process, and it is possible to achieve high optical properties.
[0050] The stretching method of the auxiliary air stretching may be fixed end stretching (for example, a method of stretching using a tenter stretching machine) or free end stretching (for example, a method of uniaxially stretching a laminate between rolls with different peripheral speeds), but in order to obtain high optical properties, free end stretching may be actively adopted. In one embodiment, the air stretching process includes a heated roll stretching process in which the laminate is stretched by the difference in peripheral speed between heated rolls while being transported in its longitudinal direction. The air stretching process typically includes a zone stretching process and a heated roll stretching process. The order of the zone stretching process and the heated roll stretching process is not limited, and the zone stretching process may be performed first, or the heated roll stretching process may be performed first. The zone stretching process may be omitted. In one embodiment, the zone stretching process and the heated roll stretching process are performed in this order. In another embodiment, the film is stretched by gripping the film end in a tenter stretching machine and widening the distance between the tenters in the flow direction (the widening of the distance between the tenters is the stretching ratio). At this time, the distance of the tenter in the width direction (perpendicular to the machine direction) is set to be as close as possible. Preferably, it can be set to be as close as possible to the free end stretching ratio in the machine direction. In the case of free end stretching, the shrinkage ratio in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.
[0051] The auxiliary air-drawing may be performed in one step or in multiple steps. When the auxiliary air-drawing is performed in multiple steps, the draw ratio is the product of the draw ratios in each step. The draw direction in the auxiliary air-drawing is preferably approximately the same as the draw direction in the underwater drawing.
[0052] The stretching ratio in the auxiliary air stretching is preferably 1.0 to 4.0 times, more preferably 1.5 to 3.5 times, and further preferably 2.0 to 3.0 times. If the stretching ratio of the auxiliary air stretching is in such a range, the total stretching ratio can be set in a desired range when combined with underwater stretching, and desired birefringence, in-plane retardation, and / or orientation function can be realized. As a result, a polarizer in which crack generation due to heating is suppressed can be obtained. Furthermore, as described above, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the underwater stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even if the total stretching ratio is small. More specifically, the ratio of the stretching ratio of the auxiliary air stretching to the stretching ratio of the underwater stretching (underwater stretching / auxiliary air stretching) is preferably 0.4 to 0.9, more preferably 0.5 to 0.8.
[0053] The stretching temperature of the auxiliary in-air stretching can be set to any appropriate value depending on the material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate + 10°C, and particularly preferably equal to or higher than Tg + 15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, rapid crystallization of the PVA resin can be suppressed, and defects due to the crystallization (for example, the orientation of the PVA resin layer due to stretching is hindered) can be suppressed.
[0054] B-2-3. Insolubilization, dyeing and crosslinking treatments If necessary, after the auxiliary air stretching treatment, an insolubilization treatment is performed before the underwater stretching treatment or the dyeing treatment. The insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. The dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). If necessary, after the dyeing treatment, a crosslinking treatment is performed before the underwater stretching treatment. The crosslinking treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Details of the insolubilization treatment, the dyeing treatment, and the crosslinking treatment are described in, for example, JP 2012-73580 A.
[0055] B-2-4. Underwater stretching process The underwater stretching treatment is performed by immersing the laminate in a stretching bath. According to the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched while suppressing crystallization. As a result, a polarizer having excellent optical properties can be produced.
[0056] The stretching method of the laminate can be any appropriate method. Specifically, it may be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate may be performed in one stage or multiple stages. When performing multiple stages, the total stretching ratio is the product of the stretching ratios in each stage.
[0057] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in boric acid water). By using an aqueous solution of boric acid as a stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, it is possible to impart rigidity and water resistance to the PVA-based resin layer and stretch it well, and to produce a polarizer with excellent optical properties.
[0058] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight, relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizer with higher characteristics can be produced. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, or the like in a solvent can also be used.
[0059] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, it is possible to suppress the elution of iodine adsorbed in the PVA resin layer. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.
[0060] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, the laminate can be stretched at a high ratio while suppressing dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a risk that the substrate cannot be stretched well even when the plasticization of the thermoplastic resin substrate by water is taken into consideration. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and there is a risk that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.
[0061] The stretching ratio in underwater stretching is preferably 1.0 to 2.2 times, more preferably 1.1 to 2.0 times, further preferably 1.1 to 1.8 times, and further more preferably 1.2 to 1.6 times. When the stretching ratio in underwater stretching is in such a range, the total stretching ratio can be set in a desired range, and the desired birefringence, in-plane retardation, and / or orientation function can be realized. As a result, a polarizer in which the occurrence of cracks due to heating is suppressed can be obtained. As described above, the total stretching ratio (the total stretching ratio when the auxiliary air stretching and the underwater stretching are combined) is preferably 3.0 to 4.5 times, more preferably 3.0 to 4.3 times, and further preferably 3.0 to 4.0 times, relative to the original length of the laminate. By appropriately combining the addition of a halide to the coating solution, the adjustment of the stretching ratios of the auxiliary air stretching and the underwater stretching, and the drying shrinkage treatment, a polarizer having acceptable optical properties can be obtained even at such a total stretching ratio.
[0062] B-2-5. Drying shrinkage treatment The drying shrinkage treatment may be performed by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll) (heat roll drying method). Preferably, both are used. By drying using a heating roll, it is possible to efficiently suppress the heat curl of the laminate and produce a polarizer with excellent appearance. Specifically, by drying the laminate in a state where it is aligned with the heating roll, it is possible to efficiently promote the crystallization of the thermoplastic resin substrate and increase the crystallinity, and even at a relatively low drying temperature, it is possible to satisfactorily increase the crystallinity of the thermoplastic resin substrate. As a result, the rigidity of the thermoplastic resin substrate increases and it becomes in a state where it can withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. In addition, by using a heating roll, it is possible to dry the laminate while maintaining it in a flat state, so that it is possible to suppress not only curling but also the occurrence of wrinkles. At this time, the optical properties of the laminate can be improved by shrinking it in the width direction by the drying shrinkage treatment. This is because the orientation of the PVA and the PVA / iodine complex can be effectively increased. The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.
[0063] 2 is a schematic diagram showing an example of the drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rolls R1 to R6 may be arranged so as to continuously heat only one surface of the laminate 200 (for example, the thermoplastic resin substrate surface).
[0064] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be favorably increased, curling can be favorably suppressed, and an optical laminate with extremely excellent durability can be produced. The temperature of the heating rolls can be measured by a contact thermometer. In the illustrated example, six transport rolls are provided, but there is no particular restriction as long as there are multiple transport rolls. The number of transport rolls is usually 2 to 40, preferably 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.
[0065] The heating roll may be provided in a heating furnace (for example, an oven) or in a normal production line (under room temperature environment). It is preferably provided in a heating furnace equipped with a blowing means. By using drying with a heating roll in combination with hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and it is possible to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. The wind speed is the wind speed in the heating furnace, and can be measured by a mini-vane type digital anemometer.
[0066] B-2-6. Other processing Preferably, after the underwater stretching treatment and before the drying shrinkage treatment, a washing treatment is carried out. The washing treatment is typically carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.
[0067] B-3.Protective layer The protective layer can be formed of any suitable material depending on the purpose.Specific examples of the protective layer forming material include cellulose resins such as triacetyl cellulose (TAC), polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, (meth)acrylic, acetate, and other transparent resins; thermosetting resins or ultraviolet curing resins such as (meth)acrylic, urethane, (meth)acrylic urethane, epoxy, and silicone; and glassy polymers such as siloxane polymers.
[0068] The protective layer may be a resin film or a solidified coating of a resin solution. When the protective layer is a resin film, the protective layer is typically attached to the polarizer via an adhesive layer. When the protective layer is a solidified coating of a resin solution, the protective layer can be formed by forming an easy-adhesion layer on the polarizer surface, applying the resin solution thereon, and solidifying the coating.
[0069] The thickness of the protective layer is preferably 2 μm to 80 μm, more preferably 5 μm to 40 μm, even more preferably 5 μm to 25 μm, and even more preferably 5 μm to 20 μm.
[0070] The protective layer is preferably substantially optically isotropic. In this specification, "substantially optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the thickness direction retardation Rth(550) is -20 nm to +10 nm. The in-plane retardation Re(550) is more preferably 0 nm to 5 nm, further preferably 0 nm to 3 nm, and particularly preferably 0 nm to 2 nm. The thickness direction retardation Rth(550) is more preferably -5 nm to +5 nm, further preferably -3 nm to +3 nm, and particularly preferably -2 nm to +2 nm. If the Re(550) and Rth(550) of the protective layer are in such ranges, adverse effects on the display characteristics can be prevented when a polarizing plate including the protective layer is applied to an image display device.
[0071] C. First retardation layer As described above, the first retardation layer 20 is an alignment-solidified layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. As a result, it is possible to realize a further reduction in thickness and weight of the retardation layer-attached polarizing plate. In this specification, the "alignment-solidified layer" refers to a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. Note that the "alignment-solidified layer" is a concept that includes an alignment-solidified layer obtained by hardening a liquid crystal monomer as described later. In this embodiment, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first retardation layer (homogeneous alignment).
[0072] Examples of liquid crystal compounds include liquid crystal compounds whose liquid crystal phase is a nematic phase (nematic liquid crystals). Examples of such liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The mechanism by which liquid crystallinity of liquid crystal compounds is expressed may be either lyotropic or thermotropic. The liquid crystal polymers and liquid crystal monomers may be used alone or in combination.
[0073] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the alignment state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other, thereby fixing the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed first retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the first retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0074] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0075] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. For example, nematic liquid crystal monomers are preferred as the liquid crystal monomer.
[0076] The alignment and solidification layer of the liquid crystal compound can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. In one embodiment, the substrate is any appropriate resin film, and the alignment and solidification layer formed on the substrate can be transferred to the surface of the polarizing plate 10. In another embodiment, the substrate can be a protective layer 12. In this case, the transfer step is omitted, and lamination can be performed by roll-to-roll immediately after the formation of the alignment and solidification layer (first retardation layer), further improving productivity.
[0077] As the above-mentioned alignment treatment, any suitable alignment treatment can be adopted. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any suitable conditions can be adopted according to the purpose.
[0078] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.
[0079] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.
[0080] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.
[0081] Another example of the alignment solidified layer is a form in which the discotic liquid crystal compound is aligned in any one of vertical alignment, hybrid alignment, and tilt alignment. The discotic liquid crystal compound is typically aligned such that the disc surface of the discotic liquid crystal compound is substantially perpendicular to the film surface of the first retardation layer. The discotic liquid crystal compound being substantially perpendicular means that the average angle between the film surface and the disc surface of the discotic liquid crystal compound is preferably 70° to 90°, more preferably 80° to 90°, and even more preferably 85° to 90°. The discotic liquid crystal compound generally refers to a liquid crystal compound having a discotic molecular structure in which a cyclic mother nucleus such as benzene, 1,3,5-triazine, or calixarene is arranged at the center of the molecule, and linear alkyl groups, alkoxy groups, substituted benzoyloxy groups, or the like are radially substituted as side chains. Representative examples of discotic liquid crystals include benzene derivatives, triphenylene derivatives, truxene derivatives, and phthalocyanine derivatives described in the research report by C. Destrade et al., Mol. Cryst. Liq. Cryst., Vol. 71, p. 111 (1981); cyclohexane derivatives described in the research report by B. Kohne et al., Angew. Chem. Vol. 96, p. 70 (1984); and azacrown and phenylacetylene macrocycles described in the research report by JM Lehn et al., J. Chem. Soc. Chem. Commun., p. 1794 (1985) and the research report by J. Zhang et al., J. Am. Chem. Soc., Vol. 116, p. 2655 (1994). Further specific examples of discotic liquid crystal compounds include those described in JP-A-2006-133652, JP-A-2007-108732, and JP-A-2010-244038, the disclosures of which are incorporated herein by reference.
[0082] In one embodiment, as shown in FIGS. 1A and 1B, the first retardation layer 20 is a single layer of an alignment solidified layer of a liquid crystal compound. When the first retardation layer 20 is composed of a single layer of an alignment solidified layer of a liquid crystal compound, its thickness is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using a liquid crystal compound, an in-plane retardation equivalent to that of a resin film can be realized with a thickness much thinner than that of the resin film.
[0083] Typically, the first retardation layer exhibits a refractive index characteristic of nx > ny = nz. Typically, the first retardation layer is provided to impart antireflection characteristics to a polarizing plate, and when the first retardation layer is a single layer of an alignment solidified layer, it can function as a λ / 4 plate. In this case, the in-plane retardation Re(550) of the first retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur.
[0084] The Nz coefficient of the first retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, when the obtained polarizing plate with a retardation layer is used in an image display device, a very excellent reflection hue can be achieved.
[0085] The first retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light. In one embodiment, the first retardation layer exhibits an inverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, very excellent antireflection characteristics can be realized.
[0086] The angle θ between the slow axis of the first retardation layer 20 and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°. If the angle θ is in such a range, by using a λ / 4 plate as the first retardation layer as described above, a retardation layer-attached polarizing plate having very excellent circular polarization properties (resulting in very excellent antireflection properties) can be obtained.
[0087] In another embodiment, the first retardation layer 20 may have a laminated structure of a first alignment solidified layer 21 and a second alignment solidified layer 22 as shown in FIG. 1C and FIG. 1D. In this case, either the first alignment solidified layer 21 or the second alignment solidified layer 22 may function as a λ / 4 plate, and the other may function as a λ / 2 plate. Therefore, the thicknesses of the first alignment solidified layer 21 and the second alignment solidified layer 22 may be adjusted so as to obtain a desired in-plane retardation of a λ / 4 plate or a λ / 2 plate. For example, when the first alignment solidified layer 21 functions as a λ / 2 plate and the second alignment solidified layer 22 functions as a λ / 4 plate, the thickness of the first alignment solidified layer 21 is, for example, 2.0 μm to 3.0 μm, and the thickness of the second alignment solidified layer 22 is, for example, 1.0 μm to 2.0 μm. In this case, the in-plane retardation Re(550) of the first alignment solidified layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 250 nm to 280 nm. The in-plane retardation Re(550) of the second alignment solidified layer is as described above for the single-layer alignment solidified layer. The angle between the slow axis of the first alignment solidified layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably about 15°. The angle between the slow axis of the second alignment solidified layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably about 75°. With such a configuration, it is possible to obtain characteristics close to ideal reverse wavelength dispersion characteristics, and as a result, it is possible to realize very excellent antireflection characteristics. The liquid crystal compounds constituting the first alignment solidified layer and the second alignment solidified layer, the methods for forming the first alignment solidified layer and the second alignment solidified layer, the optical characteristics, etc. are as described above for the single alignment solidified layer.
[0088] D. Second retardation layer As described above, the second retardation layer may be a so-called positive C plate whose refractive index characteristics show the relationship nz>nx=ny. By using a positive C plate as the second retardation layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the thickness direction retardation Rth(550) of the second retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the second retardation layer may be less than 10 nm.
[0089] The second retardation layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. The second retardation layer is preferably made of a film containing a liquid crystal material fixed in a homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0090] E. Conductive layer or isotropic substrate with conductive layer The conductive layer can be formed by forming a metal oxide film on any suitable substrate by any suitable film forming method (e.g., vacuum deposition, sputtering, CVD, ion plating, spraying, etc.). Examples of metal oxides include indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, and indium-zinc composite oxide. Among these, indium-tin composite oxide (ITO) is preferred.
[0091] When the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less. The lower limit of the thickness of the conductive layer is preferably 10 nm.
[0092] The conductive layer may be transferred from the substrate to the first retardation layer (or the second retardation layer, if present) and used alone as a constituent layer of the retardation layer-attached polarizing plate, or may be laminated with the substrate (substrate with conductive layer) to the first retardation layer (or the second retardation layer, if present). Preferably, the substrate is optically isotropic, and therefore the conductive layer can be used in the retardation layer-attached polarizing plate as an isotropic substrate with conductive layer.
[0093] Any suitable isotropic substrate may be adopted as the optically isotropic substrate (isotropic substrate). Examples of materials constituting the isotropic substrate include materials having a resin without a conjugated system, such as norbornene-based resins and olefin-based resins, as the main skeleton, and materials having a ring structure, such as a lactone ring or a glutarimide ring, in the main chain of an acrylic resin. When such materials are used, the occurrence of retardation due to the orientation of molecular chains can be suppressed to a small value when the isotropic substrate is formed. The thickness of the isotropic substrate is preferably 50 μm or less, more preferably 35 μm or less. The lower limit of the thickness of the isotropic substrate is, for example, 20 μm.
[0094] The conductive layer and / or the conductive layer of the isotropic substrate with a conductive layer may be patterned as necessary. By patterning, a conductive portion and an insulating portion may be formed. As a result, an electrode may be formed. The electrode may function as a touch sensor electrode that senses contact with the touch panel. Any appropriate method may be adopted as the patterning method. Specific examples of the patterning method include a wet etching method and a screen printing method.
[0095] F. Image display device The retardation layer-attached polarizing plate can be applied to an image display device. Therefore, the present invention includes an image display device using such a retardation layer-attached polarizing plate. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices). An image display device according to an embodiment of the present invention includes the retardation layer-attached polarizing plate on the viewing side. The retardation layer-attached polarizing plate is laminated so that the retardation layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or can be bent or folded. In such an image display device, the effect of the retardation layer-attached polarizing plate of the present invention becomes remarkable. EXAMPLES
[0096] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.
[0097] (1) Thickness The thickness was measured using an interference film thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000") The calculation wavelength range used for thickness calculation was 400 nm to 500 nm, and the refractive index was 1.53. (2) In-plane retardation of PVA (Re) For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the in-plane retardation (Rpva) of PVA at a wavelength of 1000 nm was evaluated using a retardation measurement device (manufactured by Oji Scientific Instruments, product name "KOBRA-31X100 / IR") (this is the value obtained by subtracting the in-plane retardation (Ri) of iodine from the total in-plane retardation at a wavelength of 1000 nm according to the principle explained above). The absorption edge wavelength was set to 600 nm. (3) Birefringence of PVA (Δn) The birefringence (Δn) of the PVA was calculated by dividing the in-plane retardation of the PVA measured in (2) above by the thickness of the polarizer. (4) Single unit transmittance and polarization degree For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc were measured using an ultraviolet-visible spectrophotometer (JASCO Corporation, "V-7100"). These Ts, Tp, and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. The polarization degree P was calculated from the obtained Tp and Tc using the following formula. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 It should be noted that equivalent measurements can also be made using a spectrophotometer such as the Otsuka Electronics LPF-200, and it has been confirmed that equivalent measurement results can be obtained regardless of which spectrophotometer is used. (5) Puncture strength (breaking strength per unit thickness) The polarizer was peeled off from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, and placed on a compression tester (manufactured by Kato Tech, product name "NDG5" needle penetration force measurement specifications) equipped with a needle, and pierced at a piercing speed of 0.33 cm / sec under a room temperature (23°C ± 3°C) environment. The strength at which the polarizer broke was taken as the breaking strength. The evaluation value was the average value of the breaking strengths measured for 10 sample pieces. The needle used had a tip diameter of 1 mmφ and 0.5R. The polarizer to be measured was fixed by clamping both sides of the polarizer with a jig having a circular opening with a diameter of about 11 mm, and the needle was pierced into the center of the opening to perform the test. (6) Orientation function of PVA For the polarizer (single polarizer) obtained by peeling off the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, a Fourier transform infrared spectrophotometer (FT-IR) (manufactured by Perkin Elmer, product name: "Frontier") was used to measure attenuated total reflection (ATR) spectroscopy of the polarizer surface on the surface opposite to the surface on which the resin substrate was peeled off, using polarized infrared light as the measurement light. Germanium was used as the crystallite to which the polarizer was attached, and the angle of incidence of the measurement light was 45°. The orientation function was calculated by the following procedure. The polarized infrared light (measurement light) to be incident was polarized light (s-polarized light) that vibrated parallel to the surface to which the germanium crystal sample was attached, and the absorbance spectrum of each was measured with the stretching direction of the polarizer arranged perpendicular (⊥) and parallel ( / / ) to the polarization direction of the measurement light. From the obtained absorbance spectrum, (3330 cm -1 Intensity) was used as a reference (2941 cm -1 The intensity I was calculated. ⊥ is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged perpendicular (⊥) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 In addition, I / / is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged parallel ( / / ) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 Intensity), where (2941 cm -1 Intensity) is the bottom of the absorbance spectrum, 2770 cm -1 and 2990cm -1 2941cm when using this as the baseline -1 is the absorbance of (3330cm -1 Strength) is 2990cm -1 and 3650cm -1 3330cm when the baseline is -1 The absorbance of the obtained I ⊥ and I / / The orientation function f was calculated according to formula 1. Note that f = 1 is perfect orientation, and f = 0 is random. -1 The peak is due to the main chain (-CH) of PVA in the polarizer. 2 -) vibration-induced absorption. -1 The peak is said to be due to the vibration of the hydroxyl group of PVA. (Formula 1)f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] however c = (3cos 2 β-1) / 2 So, as mentioned above, 2941cm -1 When using this function, β=90°⇒y=-2×(1-D) / (2D+1). θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I ⊥ ) / (I / / ) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel (7) Crack occurrence rate The retardation layer-attached polarizing plates obtained in the examples and comparative examples were cut into a size of 10 mm x 10 mm. The cut retardation layer-attached polarizing plates were attached to a glass plate (thickness 1.1 mm) via an acrylic adhesive layer having a thickness of 20 μm so that the retardation layer side was on the glass plate side. The sample attached to the glass plate was placed in an oven at 100° C. for 120 hours, and then visually confirmed whether or not cracks occurred in the absorption axis direction (MD direction) of the polarizer. This evaluation was performed using three retardation layer-attached polarizing plates, and the number of retardation layer-attached polarizing plates in which cracks occurred was evaluated.
[0098] [Example 1] 1. Preparation of polarizing plate (polarizer) The thermoplastic resin substrate was a long, amorphous, isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) with a water absorption rate of 0.75% and a Tg of approximately 75°C. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W min / m 2 ) was applied. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizer would be 40.5% (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0 wt %, potassium iodide 5.0 wt %) at a liquid temperature of 62°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretching ratio was 3.0 times (underwater stretching treatment: the stretching ratio in the underwater stretching treatment was 1.25 times). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, it was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for about 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 2%. In this manner, a polarizer having a thickness of 7.4 μm was formed on the resin substrate.
[0099] 2. Preparation of the first alignment layer and the second alignment layer constituting the retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90°C for 2 minutes. The liquid crystal layer thus formed was then irradiated with 100 mJ / cm using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal layer with light of 1000 nm to form a first alignment solidified layer on the PET film. The first alignment solidified layer had a thickness of 2.5 μm and an in-plane retardation Re(550) of 270 nm. Furthermore, the first alignment solidified layer had a refractive index distribution of nx>ny=nz. A second alignment solidified layer was formed on a PET film in the same manner as above, except that the coating thickness was changed and the alignment treatment direction was set to a 75° direction relative to the absorption axis direction of the polarizer when viewed from the viewing side. The thickness of the second alignment solidified layer was 1.3 μm, and the in-plane retardation Re(550) was 140 nm. Furthermore, the second alignment solidified layer had a refractive index distribution of nx>ny=nz.
[0100] 3. Preparation of polarizing plate with retardation layer The first alignment solidified layer and the second alignment solidified layer obtained in the above 2 were transferred in this order onto the polarizer surface of the laminate having the configuration of [polarizer / resin substrate] obtained in the above 1. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizer and the slow axis of the first alignment solidified layer was 15°, and the angle between the absorption axis of the polarizer and the slow axis of the second alignment solidified layer was 75°. Note that each transfer (lamination) was performed via an ultraviolet-curable adhesive (thickness 1.0 μm). The resin substrate was peeled off from the obtained laminate to obtain a retardation layer-attached polarizing plate having a configuration of [polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer)]. The total thickness of the obtained retardation layer-attached polarizing plate was 13.2 μm.
[0101] [Examples 2 to 4] A polarizer (thickness: 7.4 μm) was formed on a resin substrate in the same manner as in Example 1, except that a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the structure of [polarizer / resin substrate], a polarizing plate with a retardation layer having a structure of [polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer)] was obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 13.2 μm.
[0102] [Examples 5 to 8] A polarizer (thickness: 6.7 μm) was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was 1.46 times (resulting in a total stretching ratio of 3.5 times) and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the structure of [polarizer / resin substrate], a polarizing plate with a retardation layer having the structure of [polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer)] was obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 12.5 μm.
[0103] [Examples 9 to 12] A polarizer (thickness: 6.2 μm) was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was 1.67 times (resulting in a total stretching ratio of 4.0 times) and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the structure of [polarizer / resin substrate], a polarizing plate with a retardation layer having a structure of [polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer)] was obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 12.0 μm.
[0104] [Examples 13 to 16] A polarizer (thickness: 6.0 μm) was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was 1.88 times (resulting in a total stretching ratio of 4.5 times) and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the structure of [polarizer / resin substrate], a polarizing plate with a retardation layer having a structure of [polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer)] was obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 11.8 μm.
[0105] [Comparative Examples 1 to 4] A polarizer (thickness: 5.5 μm) was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was 2.29 times (resulting in a total stretching ratio of 5.5 times) and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the structure of [polarizer / resin substrate], a polarizing plate with a retardation layer having the structure of [polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer)] was obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 11.3 μm.
[0106] The retardation layer-attached polarizing plates or polarizers obtained in the Examples and Comparative Examples were subjected to the above evaluations (2) to (7). The results are shown in Table 1.
[0107] [Table 1]
[0108] As is clear from Table 1, the retardation layer-attached polarizing plates of the Examples did not include a protective layer and had an extremely thin structure, but the occurrence of cracks due to heating was suppressed.
[0109] 3 to 5 show the relationship between the single transmittance of the polarizer obtained in the examples and the comparative examples and the Δn, in-plane retardation, or orientation function of PVA. As shown in FIG. 3 to FIG. 5, even if the birefringence, in-plane retardation, or orientation function are similar (resulting in the same degree of orientation), when the single transmittance is high, cracks are likely to occur due to heating. Therefore, in order to effectively suppress the occurrence of cracks due to heating, it is important to adjust the single transmittance (resulting in the amount of adsorption of the dichroic material) in addition to the degree of orientation of the PVA-based resin. Also, it is found that the polarizer satisfying formula (1), formula (2), and / or formula (3) is one in which these adjustments have been suitably performed, and the occurrence of cracks due to heating can be suitably suppressed. [Industrial Applicability]
[0110] The retardation layer-attached polarizing plate of the present invention is suitably used in an image display device. [Explanation of symbols]
[0111] 10 Polarizing plate 11 Polarizer 20 Retardation layer 100 Polarizing plate with retardation layer
Claims
[Claim 1] A polarizing plate including a polarizer and a retardation layer provided on one side of the polarizing plate, the polarizing plate does not include a protective layer on the side of the polarizer opposite to the side on which the retardation layer is provided, the retardation layer is a layer in which a liquid crystal compound is aligned and solidified, The polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic material, and satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin is y. y<-0.011x+0.525 (1)
Citation Information
Patent Citations
Polarizing plate and method for manufacturing the same
JP2001343521A